2019
DOI: 10.1002/jsfa.10115
|View full text |Cite
|
Sign up to set email alerts
|

Regulation mechanism of silkworm pupa oil PUFAs on cholesterol metabolism in hepatic cell L‐02

Abstract: BACKGROUND: Silkworm pupa oil polyunsaturated fatty acid (SPO PUFA) has been confirmed to have a cholesterol-lowering function. METHODS AND RESULTS:The effect of SPO PUFA and its main component, -linolenic acid (ALA), on the metabolism of cholesterol and its regulation was investigated. The model of lipid denatured cells were constructed to carry out lipid accumulation, cholesterol metabolism and transformation. Real-time PCR and western blots were also used to analyze the expression levels of related genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…Zou et al (2017) described that silkworm pupae are sources of polyunsaturated fatty acids at 60-70% of total fat contents. In this study, the most abundant fatty acid was oleic acid (C18:1) (n-9), followed by alpha-linolenic acid, ALA, (C18:3) (n-3) and linoleic acid (C18:2) (n-6), respectively (Tables 3 and 4), as also observed by Luo et al (2020). ALA is known as a precursor to both eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which have shown vital physiological roles in human brain development and cardiovascular health (Ji et al, 2016;Luo et al, 2020).…”
Section: Nutritional Valuessupporting
confidence: 81%
See 1 more Smart Citation
“…Zou et al (2017) described that silkworm pupae are sources of polyunsaturated fatty acids at 60-70% of total fat contents. In this study, the most abundant fatty acid was oleic acid (C18:1) (n-9), followed by alpha-linolenic acid, ALA, (C18:3) (n-3) and linoleic acid (C18:2) (n-6), respectively (Tables 3 and 4), as also observed by Luo et al (2020). ALA is known as a precursor to both eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which have shown vital physiological roles in human brain development and cardiovascular health (Ji et al, 2016;Luo et al, 2020).…”
Section: Nutritional Valuessupporting
confidence: 81%
“…In this study, the most abundant fatty acid was oleic acid (C18:1) (n-9), followed by alpha-linolenic acid, ALA, (C18:3) (n-3) and linoleic acid (C18:2) (n-6), respectively (Tables 3 and 4), as also observed by Luo et al (2020). ALA is known as a precursor to both eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which have shown vital physiological roles in human brain development and cardiovascular health (Ji et al, 2016;Luo et al, 2020). Therefore, it seems that silkworm pupae may be considered as a quality source of protein and lipid for human and could be used in the food industry as a nutritious additive in foods and beverages.…”
Section: Nutritional Valuessupporting
confidence: 81%
“…CYP7A1, an important enzyme for the conversion of cholesterol into bile acids, is a biomarker for reverse cholesterol transport ( Chen and Huang, 2009 ). Several studies have reported that PPARγ regulates the expression of CYP7A1, which suggests that miR-27b/PPARγ/CYP7A1 might comprise a pathway that regulates the metabolism of both cholesterol and polyunsaturated fatty acids ( Ge et al, 2017 ; Han et al, 2019 ; Luo et al, 2019 ). Our data demonstrated that elevated PPARγ levels enhanced the mRNA and protein expression of CYP7A1, which may promote the reverse transport of cholesterol in skeletal muscle while lowering the accumulation of total cholesterol in the blood ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of edible insects on coagulation markers (37)(38)(39) , inflammatory status (41,46) and lipid metabolism (7,(47)(48)(49) are described in Table 5. A total of eleven studies involving eight insects were reported: Protaetia brevitaris was cited in three research articles, whilst Oxya chinensis, Gryllus bimaculatus and Tenebrio molitor were investigated in two studies each.…”
Section: Other Activity In Cellular Models or Ex Vivomentioning
confidence: 99%
“…In four studies (7,(47)(48)(49) , the ability of edible insects to modulate lipid pattern in cellular models was investigated through evaluation of lipid content or the expression of genes related to lipid metabolism. Ethanolic extract of Gryllus bimaculatus, Oxya chinensis sinuosa and Protaetia brevitarsis seulensis diminished intracellular lipid accumulation and triacylglycerol (TG) in HepG2, a human liver cancer cellular line (47) .…”
Section: Other Activity In Cellular Models or Ex Vivomentioning
confidence: 99%